Resoconto sul «Congreso Universidad 2010», 8-12 febrero 2010, Cuba, Palacio de Convenciones de La Habana - Luciano Vasapollo (LED Edizioni Universitarie, 2010)
The «Congreso Universidad 2010», held in Palacio de Convenciones de La Habana, Havana (Cuba) on 8-12 February, was an opportunity for scientific and cultural debate as well as for exchanges between universities of all over the world. Representatives from as many as 64 countries dealt with this year's theme «for a better world», which alluded to the importance of putting public knowledge back to the heart of public university research. The conference was arranged into different parallel seminars to make the development of various scientific activities possible, in the form of conferences, presentations, panels, poster sessions and work sessions, and developed 13 work sections on themes dealing with engineering, medicine, economics, social sciences, humanities and technology. The conference also aimed to favour and continue exchanges between the delegations representing universities all over the world, by offering a useful opportunity to establish international agreements and promote the internationalisation strategies implemented by universities.